Magnetic Nanoparticles for Targeting and Imaging of Stem Cells in Myocardial Infarction - Michelle R. Santoso; Phillip C. Yang (Stem Cells International)
Stem cell therapy has broad applications in regenerative medicine and increasingly within cardiovascular disease. Stem cells have emerged as a leading therapeutic option for many diseases and have broad applications in regenerative medicine. Injuries to the heart are often permanent due to the limited proliferation and self-healing capability of cardiomyocytes; as such, stem cell therapy has become increasingly important in the treatment of cardiovascular diseases. Despite extensive efforts to optimize cardiac stem cell therapy, challenges remain in the delivery and monitoring of cells injected into the myocardium. Other fields have successively used nanoscience and nanotechnology for a multitude of biomedical applications, including drug delivery, targeted imaging, hyperthermia, and tissue repair. In particular, superparamagnetic iron oxide nanoparticles (SPIONs) have been widely employed for molecular and cellular imaging. In this mini-review, we focus on the application of superparamagnetic iron oxide nanoparticles in targeting and monitoring of stem cells for the treatment of myocardial infarctions.